SPACE USE AND MOVEMENTS OF MOOSE IN MASSACHUSETTS: IMPLICATIONS FOR CONSERVATION OF LARGE MAMMALS IN A FRAGMENTED ENVIRONMENT - Wattles, David W.; DeStefano, Steven (Lakehead University, 2013)
Moose (Alces alces) have recently re-occupied a portion of their range in the temperate deciduous forest of the northeastern United States after a >200 year absence. In southern New England, moose encounter different forest types, more human development, and higher temperatures than in other parts of their geographic range in North America. We analyzed seasonal minimum convex polygon home ranges, utilization distributions, movement rates, and home range composition of GPS-collared moose in Massachusetts. Seasonal home range sizes were not different for males and females and were within the range reported for low latitudes elsewhere in North America. Seasonal movement patterns reflected the seasonal changes in metabolic rate and the influence of the species’ reproductive cycle and weather. Home ranges consisted almost entirely of forested habitat, included large amounts of conservation land, and had lower road densities as compared to the landscape as a whole, indicating that human development may be a limiting factor for moose in the region. The size and configuration of home ranges, seasonal movement patterns, and use relative to human development have implications for conservation of moose and other wide-ranging species in more highly developed portions of their ranges.